Virtual Reality Efektif Menurunkan Kecemasan Ibu Primigravida Trimester III dalam Menghadapi Persalinan (Journal of Telenursing (JOTING), 2022)
This study aims to determine the effect of virtual reality on the anxiety of third-trimester primigravida in facing childbirth. The method used is experimental, with a one-group pre-post test design approach carried out at the Putri Ayu Health Center involving 34 mothers. The results showed that before the intervention, the data obtained for mild anxiety was 58.9%, moderate was 38.2% and severe was 2.9%, while after the intervention, the percentage of mild anxiety was 82.4% and moderate = 17.6%. The statistical test results obtained are equal to 0.001. In conclusion, there is an effect of virtual reality on decreasing the anxiety level of a third-trimester primigravida in facing childbirth. Keywords: Maternal Anxiety, Childbirth, Primigravida, Virtual Reality